ASLIB Cranfield Research Project: report on the first stage of an investigation into the comparative efficiency of indexing systems - Cleverdon, Cyril W. (College of Aeronautics, Cranfield, 1960)
It was in 1953 that the train of events started which brought about my participation in the investigation which is the subject of this report. R. G. Thorne, of the Royal Aircraft Establishment, and I had been closely associated with the development of the Nationaal Luchtvaart- laboratorium Card Catalogue of Aerodynamic Data (Ref.1). This was an index designed for the retrieval of information in answer to very specific requests, and was far removed from the systems used in conventional library indexing. In that the average time taken to index each document was 1.5 hours, it was comparatively expensive, although the cost was shared out on a subscription basis amongst a number of organisations. Clearly, however, such an index could only be used for a relatively limited range of documents that were of particular significance, and Thorne and I were prepared to accept the possibility that in certain circumstances an organisation might be economically justified in maintaining two different types of indexes covering an overlapping range of documents. The Universal Decimal Classification was widely used in England and, in spite of many criticisms, was on the whole meeting the requirements of its users for a general indexing system. We were looking for another system which would fulfil the same function as the NLL scheme, but which might be less expensive and therefore more attractive economically for a single organisation to operate.